Ego Defense Mechanisms in Dominic Toretto's Character: A Psychoanalytic Analysis of The Fate of The Furious - Andhika Prayata Saputra Hardiyanto; Agnes Widyaningrum (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study explores the ego defense mechanisms in Dominic Toretto’s character in The Fate of The Furious (2017), aiming to bridge the gap in understanding how psychological depth can operate within the narrative constraints of action cinema. Using Freudian psychoanalytic theory as the analytical framework, the research applies qualitative content analysis through a context-oriented approach. It examines how psychological responses unfold within the film’s narrative structure, genre conventions, and cultural values. The analysis focuses on selected scenes, character dialogue, and cinematic techniques to identify expressions of Toretto’s personality structure—Id, Ego, and Superego—and five key defense mechanisms: rationalization, suppression, displacement, isolation of affect, and sublimation. Findings show that Toretto’s psychological structure reflects a dynamic interplay between primal instincts (Id), rational mediation (Ego), and internalized morality (Superego). This interplay creates intense psychological tension, requiring a set of ego defenses to manage internal conflict. Each mechanism serves a distinct adaptive function, translating emotional distress into calculated action. For instance, rationalization justifies morally ambiguous decisions, while sublimation channels emotional turmoil into mission success. These mechanisms allow Toretto to navigate high-stakes situations, balance conflicting loyalties, and maintain both operational and emotional stability. The study concludes that action films can successfully integrate psychological complexity without diminishing entertainment value. Defense mechanisms serve not only as coping strategies but also as narrative tools that highlight emotional resilience and moral ambiguity. By applying a systematic psychoanalytic framework to an action hero, this research offers a new methodological model for character analysis in genre cinema. Moreover, it shows how psychological elements reflect contemporary cultural ideals, particularly concerning family loyalty, sacrifice, and emotional endurance in modern society.